Financial hardship and the intensity of medical care received near death. Issue 5 (23rd July 2014) - Tucker‐Seeley, Reginald D.; Abel, Gregory A.; Uno, Hajime; Prigerson, Holly
Abstract Background Although end‐of‐life (EOL) care can present a substantial financial burden for the household, the influence of this burden on the intensity of care received at the EOL remains unknown. The goal of this study was to determine the association between financial hardship and intensive care in the last week of life. Methods The Coping with Cancer (CwC) Study is a longitudinal, multisite cohort study of terminally ill cancer patients and their informal caregivers, September 2002–February 2008. Patients (N = 281) were followed from baseline to death, a median of 4.4 months after baseline assessment. Intensive care was defined as the use of resuscitation and/or ventilation in the patient's last week of life. Financial hardship was measured at study baseline as a positive response to whether the household had to use all or most of their savings because of the family member's illness. Results Twenty‐nine percent reported financial hardship, and 9% received intensive EOL care. Patients reporting financial hardship had a 3.22 (95% CI: 1.38, 7.53) higher likelihood of receiving intensive EOL care compared with patients not reporting financial hardship. After adjusting for sociodemographic characteristics and patient preferences, patients reporting financial hardship had a 3.05 (95% CI: 1.22, 7.62) higher likelihood of receiving intensive EOL care. Conclusion The depletion of a family's financial resources is a significant predictor of intensive EOL care, over and above the influence of sociodemographic characteristics and patient preferences. Copyright © 2014 John Wiley & Sons, Ltd.